Pengaruh Kualitas Perpustakaan Digital Terhadap Prestasi Belajar Mahasiswa (Studi Kasus pada Universitas Islam Indonesia) - Sungadi Sungadi (Institut Agama Islam Negeri Salatiga, 2021)
The library is a source of life long learning and has an important role process in higher education. This study intends to test and prove the quality of digital libraries on student learning achievement. The research method uses a descriptive quantitative approach with a sample of Indonesian Islamic University (UII) students who submitted free literature as a condition for registering graduation month January-March 2020 a total of 126 students. Sampling using a non-probability method by means of convenience sampling. Data analysis used descriptive analysis and multiple regression. The results showed that partially there were 4 accepted hypotheses and 3 rejected hypotheses. The accepted hypotheses are: H1: the quality of digital libraries (X) on academic achievement (Y). H2: system development (X1) on Academic Achievement (Y). H3: means of promotion (X2) on academic achievement (Y). H5: means of sharing information (X4) on academic achievement (Y). While the rejected hypothesis is H4: deposit and preservation function (X3) on academic achievement (Y). H6: collaboration between institutions (X5) on academic achievement (Y). H7: online learning resources (X6) on academic achievement (Y). Furthermore, from the results of Multiple Regression Analysis, it is proven that simultaneously variables X, X1, X2, X3, X4, X5 and X6 have an effect on variable Y with an effect of 57.4%, while the remaining 42.6% is influenced by other factors whose variables are not studied in this study. The recommendation given is the need for improvements in the dimensions of e-learning learning resources and the dimensions of meeting information needs in the field of entertainment and recreation for users.